it is true that , but that is a totally different situation from what we have here. we have something like , different things come into play here. that being said, your answer is incorrect. don't try anything fancy, just take the of both sides and work it out using regular algebraic manipulation. because you would need to change the function a bit to use the rule, and to me, it's not worth it here.
so: k=(about) -1.2054 x 10^-4 and
.777= e ^kt --> ln both sides
ln (.777) = ln (e ^kt) --> Today i friend old me you could bring the kt down like:
ln (.777) = Kt ln(e) --> If thats correct then t = 2093.077..
is that right :-s?
Edit: If bringing down the exponent is right can someone explain why you're allowed to do that?
You can indeed bring the exponent down. The definition of a log is:so: k=(about) -1.2054 x 10^-4 and
.777= e ^kt --> ln both sides
ln (.777) = ln (e ^kt) --> Today i friend old me you could bring the kt down like:
ln (.777) = Kt ln(e) --> If thats correct then t = 2093.077..
is that right :-s?
Edit: If bringing down the exponent is right can someone explain why you're allowed to do that?
if then
also implies that , so
but so